A Cross-National Analysis of Alcohol Consumption and Suicide Rates: Variations by Population-Level Drinking Patterns. (October 2019) - Testa, Alexander; Weiss, Douglas B.; Rennó Santos, Mateus
This study assesses the association between the population-level consumption of different types of alcohol and cross-national suicide rates and examines whether this association is moderated by country-specific drinking patterns. We apply negative binomial regression to test whether the consumption of beer, wine, or spirits is predictive of suicide rates. Next, we use interaction terms to examine whether the effect of beverage-specific consumption on suicide rates is moderated by total alcohol consumption, prevalence of consumption, or the riskiness of drinking patterns. We find that only spirit consumption has a positive and statistically significant association with suicide rates. The effect of spirit consumption on suicide is higher among countries where the total alcohol consumption and the prevalence of alcohol consumption are lower, and patterns of drinking are riskier. Future research should continue to investigate this relationship to develop interventions that reduce suicide mortality related to alcohol use.